Optimisation of eddy current thermography for defect detection on selected steel specimens - Rusli, Nurliyana Shamimie (2017)
Eddy current thermography is one of the non-destructive testing techniques that provide advantages over other active thermography techniques in terms of defect detection and analysis. The method of defect detection in eddy current thermography has become reliable due to its mode of interactions, such as, eddy current heating and heat diffusion, acquired via an infrared camera. Such ability has given advantages for non-destructive testing applications. The experimental parameters and settings which contributed towards optimum heating and defect detection capability have always been the focus of research. In addition, the knowledge and understanding of the characteristics heat distribution surrounding a defect is an important factor for successful inspection results. Thus, the qualitative characterisation of defect by this technique appears to have advantages to the conventional non-destructive testing. This thesis focuses on the theoretical and experimental investigation, specifically in investigating the transient response and temperature distribution to the presence of defects. Signal to Noise Ratio (SNR) analysis is applied on the Austenitic Stainless Steel SS316 to identify the parameters which will prevail the most significant indication of defect by performing the optimisation parameter of heating time and excitation current applied. The outcome from the optimisation of SNR is beneficial to apply on the investigation of subsurface defect at area of HAZ, toe and root region. Numerical simulations of Comsol FEM Multiphysics concerning the visualisation of the resulting transient responses from eddy current due to the occurrence of the underlying phenomenon of eddy current interaction with defects was simulated. Angular defects of 00, 250and 450 prevail that, greater angle of a defect will cause the amplitude of the linescan profile to become more slanted and a higher temperatureamplitude of the angle is acquired respectively. Furthermore, internal defect of different depths proves that the increase in depth of defects will cause the amplitude of the temperature profiles to decrease. The investigation for different sizes of defect stimulate a higher temperature at the surface of the specimen for the bigger sizes of defect. The results of the experimental investigation is compared with the numerical simulation results to provide comprehensive verification towards the investigation.